2008
DOI: 10.1029/2008gl035724
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory seismoelectric measurement for the permafrost model with a frozen–unfrozen interface

Abstract: [1] In this study, a laboratory seismoelectric measurement for the permafrost model with a frozen -unfrozen interface is presented. The measurements obtained experimentally confirms that an electric double-layer can be formed at the interface due to the electric and mechanical differences of the frozen and unfrozen media, and seismoelectric conversion EM waves originted from the relative motion of the charges in the electric double-layer can be observed at n  10 kHz frequency band. This suggests a potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…This observation could be related to increasing bulk conductivity (Block and Harris, 2006) and/or incomplete equilibration of the electric double layer. For silica, the electric double layer may take several days to become stable (Morgan et al, 1989), and it may take hours at soil interfaces (Liu et al, 2008). One could also speculate on the electrodes developing a voltage drop at their surface, thus reducing the measured amplitudes over time.…”
Section: Salinity (M Naclmentioning
confidence: 99%
“…This observation could be related to increasing bulk conductivity (Block and Harris, 2006) and/or incomplete equilibration of the electric double layer. For silica, the electric double layer may take several days to become stable (Morgan et al, 1989), and it may take hours at soil interfaces (Liu et al, 2008). One could also speculate on the electrodes developing a voltage drop at their surface, thus reducing the measured amplitudes over time.…”
Section: Salinity (M Naclmentioning
confidence: 99%
“…The generation of these EM fields has been investigated in detail by Hu [], who demonstrated that they result from the inhomogeneous EM waves that are generated by the corresponding seismic waves at the borehole wall. Such inhomogeneous EM waves have also been theoretically modeled for a solid/porous‐medium configuration [ Ren et al ., ] and observed in laboratory experiment for the permafrost model with a frozen‐unfrozen interface [ Liu et al ., ]. In both studies, EM signals accompanying seismic waves were observed at receivers that are located in the solid region near the interface.…”
Section: Introductionmentioning
confidence: 99%
“…This observation could be related to increasing bulk conductivity (Block & Harris, 2006) and/or incomplete equilibration of the electric double layer. For silica, the electric double layer may take several days to become stable (Morgan et al, 1989), and it may take hours at soil interfaces (Liu et al, 2008). One could also speculate on the electrodes developing a voltage drop at their surface, thus reducing the measured amplitudes over time.…”
Section: Comparison Between Experiments and Forward Modelmentioning
confidence: 99%
“…Full-waveform electroseismic simulations were performed by White & Zhou (2006); Hu et al (2007); Guan & Hu (2008) and Zyserman et al (2010). A wide range of field and laboratory measurements of the coseismic and interface response fields was presented (see e.g., Martner & Sparks, 1959;Thompson & Gist, 1993;Butler et al, 1996;Mikhailov et al, 1997;Beamish, 1999;Zhu et al, 1999;Mikhailov et al, 2000;Zhu et al, 2000;Garambois & Dietrich, 2001;Zhu & Toksöz, 2003, 2005Block & Harris, 2006;Bordes et al, 2006;Dupuis & Butler, 2006;Haines et al, 2007;Dupuis et al, 2007;Strahser et al, 2007;Liu et al, 2008;Zhu et al, 2008a,b;Dupuis et al, 2009). Zhu & Toksöz (2005) and Bordes et al (2006Bordes et al ( , 2008 reported on coseismic magnetic field measurements associated with a Stoneley wave and a shear wave, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%